A Preliminary Evaluation of the Effects of a Contingency Management + Deposit Contract Intervention on Problematic Smartphone Use With College Students. Issue 2 (March 2023) - Williams-Buttari, Devin; Deshais, Meghan A.; Reeve, Kenneth F.; Reeve, Sharon A.
Problematic smartphone use (PSU) is smartphone usage that is, in some way, damaging to the user. PSU represents a growing public health concern that could be addressed via behavioral intervention. We recruited six college students who reported negative side effects of smartphone use and sought to decrease their PSU. The effects of a contingency management (CM) + deposit contract intervention on PSU was evaluated. During the CM + deposit contract condition, participants deposited 40 and had the opportunity to earn back their entire deposit by meeting daily smartphone usage goals. To promote adherence to study protocols, participants also had the opportunity to earn a 20 cooperation bonus. For all participants, lower levels of PSU were observed during intervention relative to baseline. The CM + deposit contract intervention produced consistent decreases in PSU for four participants (mean reduction percentages above 40% were obtained) and had inconsistent effects on PSU for two participants (mean reduction percentages below 20%). Maintenance of intervention effects was limited for all participants. Although preliminary, results suggest that CM + deposit contract interventions could be a viable, low-cost approach to addressing PSU. Potential explanations for our findings and avenues for future research are discussed.